(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
Inclusive education has increasingly been recognized as more than a pedagogical reform aimed at integrating learners with disabilities into mainstream classrooms. This article conceptualizes inclusive education as a multidimensional cultural and ethical paradigm embedded within contemporary societal transformation. Drawing on a qualitative, theory-driven analytical approach, the study synthesizes perspectives from the social model of disability, ethics of justice and care, and cultural transformation theory. The analysis identifies three interdependent dimensions of inclusion: structural (institutional policies and accessibility), cultural (reframing societal perceptions of difference), and ethical (justice, dignity, and collective responsibility). The findings suggest that inclusive education cannot be effectively implemented through policy reform alone. Sustainable inclusion requires alignment between institutional structures, cultural consciousness, and moral commitment. In contexts characterized by globalization and digitalization, inclusive education also functions as a normative framework that prevents modernization from reinforcing inequalities. By interpreting inclusion as a paradigm rather than a technical program, this study contributes to theoretical debates in educational and humanitarian scholarship and provides a conceptual model for understanding inclusive transformation in contemporary societies.